Implementasi Manajemen Kelas dan Dampaknya Terhadap Hasil Belajar Siswa Mata Pelajaran Pendidikan Agama Islam - Siti Aisah (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2020)
This article aims to determine the implementation of the management of the PAI teacher class at JHSPalembang and to determine student learning outcomes and the impact of classroom management on learning outcomes. This study uses a qualitative approach to data collection techniques, namely in-depth interviews, observations, and documentation. Then the data analysis technique used is non-statistical analysis suitable for descriptive or textular data which is not realized in the form of numbers. The results of the study stated that the implementation of the management of the PAI teacher class at JHS Palembang from the results of classroom observations was good. Several indicators of class management implementation only 3 (three) indicators did not reach 100%, namely the layout of tables and chairs, attention to class plans andverbal reinforcement. Student learning outcomes PAI Subjects are good. Based on the documentation study of 3 (three) daily tests, 100% of the teachers (4 people) succeeded in increasing the average value significantly even though there was one class, namely class VII.5 which on the 3rdday of the test decreased but there was no effect if seen from students' mastery learning based on the Minimum Mastery Criteria (KKM) set at the beginning of the school year. The implementation of teacher classroom management has an impact on student learning outcomes, especially in the PAI subjects atJHSPalembang. The better the application of classroom management, the better the learning outcomes.